To pieces - Darcangelo, Vince, author; Doenges, Judy, advisor; Schwartz, Stephen, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2012)
To Pieces is the first-person narrative of therapist Victor Donaldson, whose tale begins in a rural Minnesota farmhouse. A month earlier, he and his wife, Simi, left Colorado following Vic's nervous breakdown. Their intended length of stay is uncertain, though they need to return to Boulder soon. Vic, who suffers from obsessive-compulsive disorder, which he calls "The Disquiet," attempts to retrace the roots of his breakdown by revisiting his chart notes on a former client. He believes he can fix his broken past by reliving, and revising, his notes. Through them, we see the arc of his breakdown beginning with his first session with Px--a man so much like Vic that the chart notes might as well be about himself. But when the true reason for his fleeing to Minnesota is revealed, and Simi realizes the dark truth Vic has kept hidden from her, he is forced to re-enter the world that terrifies him. What stability he's built at the farmhouse crumbles and he retreats to the hayloft where he confronts the truth of who he is and what he's become--and must decide if he can live with knowledge.